The Influence of Organisational Culture and Knowledge Sharing on Employee Performance at PT XYZ - Ghulam Ilmam H; Anita Silvianita; Arry Widodo; Nurafni Rubiyanti (PT FORMOSA CENDEKIA GLOBAL, 2024)
Human Resources has become something that absolutely must be owned by the company, because humans are the only human resources that have the ability, experience, reason, knowledge and creativity. PT XYZ has long been a leading textile producing company and has imported its production goods to countries in Asia. in the production process, PT XYZ is supported by several departments with different functions, so it is necessary for the company to have a strong organizational culture and application of knowledge sharing. This study aims to analyze the performance of employees at PT XYZ. This study uses variables of organizational culture and knowledge sharing to analyze the effect on employee performance. The method used in this study is a quantitative method with a descriptive type of research. In this study the sample collection using probability sampling technique with simple random sampling and the number of respondents as many as 286 people from all employees at PT XYZ using structural equation modeling (SEM) analysis.